Growth of human digestive-tumour xenografts in athymic nude rats. - Davies, G. (Nature Publishing Group, 1981)
The athymic nude rat rnu/rnu has been established as an in vivo model for the acceptance of human digestive-tumour xenografts. We report the successful xenografting of 7/12 (58%) primary explants from patients with digestive cancer. Successful xenografting also occurred in 21/25 (84%) pancreatic tumours derived from a pancreatic exocrine adenocarcinoma (GER) maintained in cell culture; 2 of those have been successfully passaged in nude rats. The simultaneous implantation of these tumours into nude mice led to an almost identical take rate. Passage of one colonic and one pancreatic xenograft from nude rats into nude mice, and transplantation back into nude rats, increased the take rates. The critical period for the establishment of primary tumour growth was usually 28-42 days. The xenografts maintained histological and cytological characteristics of the primary explants or of the original tumour from which the cell line derived. The karyotype of the cell line was also maintained in the solid tumour. Three murine tumours were successfully grown as xenografts. Despite their immunoincompetence, the rats in this study showed no increased morbidity or mortality when kept in conventional conditions, compared with animals housed in isolators. The athymic nude rat will become a valuable complementary tool to the nude mouse for the establishment and maintenance of human digestive tumours and for surgical and serial serological studies. IMAGES: